مصنوعی ذہانت (اےآئ) کے اخلاقی و فقہی پہلو: اسلامی اصولوں کی روشنی میں ایک تنقیدی جائزہ: Ethical and Jurisprudential Aspects of Artificial Intelligence (AI): A Critical Review in the Light of Islamic Principles - Bukhari, Dr. Syed Muhammad Haroon Shah (Al-Irfan, 2025)
Artificial Intelligence (AI) is one of the most significant scientific and technological developments of the modern era, profoundly influencing almost every aspect of human life. While AI offers unprecedented opportunities for efficiency, convenience, and innovation, it simultaneously raises complex ethical, social, and jurisprudential questions. This study critically examines AI through the lens of Islamic ethics and jurisprudence. Key issues discussed include human free will and accountability, the distinction between halal and haram, privacy concerns, employment challenges, military applications, and AI’s role in judicial and economic systems. The research aims to demonstrate how Islamic law can provide a moral framework that ensures the beneficial use of AI for humanity. Drawing upon the Qur’an, Sunnah, classical juristic maxims (such as la darar wa la dirar and al-darurat tubih al-mahzurat), and insights from contemporary Muslim scholars, the paper proposes an integrated framework for engaging with AI. The conclusion reached is that AI, in itself, is permissible (mubah), but its usage must conform to the objectives of Shariah (maqasid al-shari‘ah) and ethical boundaries.